Peran komunikasi dalam mempopulerkan branding dan reputasi organisasi - Alisa, Siti Nur (Maliki Interdisciplinary Journal, 2025)
Every human being will certainly use communication to convey some information, opinions or other statements, communication is not only done verbally, but can be used using speech, writing, sentences, body gestures, or through social media. Communication is a design used to be used as a liaison between internal and external parties. Good communication is proven by the clarity of the vision and mission and the honesty of an organization in conveying something to external parties, with good and effective communication will have a wide impact on the organization in improving its image, reputation and branding image. Thus, in communicating everyone will use strategies so that communication runs smoothly, one of which is transparency to external parties. In today’s era with the development of technology that can utilize social media as a virtual communication tool from the organization to external parties, such as introducing several programs or the structure of the organization itself. Communication skills are important skills to master with good communication will also build good relationships.